Immature stages of Homophileurus tricuspis Prell (Coleoptera: Scarabaeidae: Dynastinae: Phileurini) with notes on natural history and distribution in Colombia - Moreno, Jhon César Neita; Ratcliffe, Brett C. (Zootaxa, 2011)
The larva and pupa of Homophileurus tricuspis Prell (Coleoptera: Scarabaeidae: Dynastinae: Phileurini) are described for the first time based on specimens from Colombia. A key to the known third-stage larvae of New World Phileurini species is provided. Notes on the natural history and distribution of H. tricuspis in Colombia are also included.